Mapping my return : a Palestinian memoir - Abu-Sitta, Salman H. (Cairo : American University in Cairo Press, 2016)
Refugees, Palestinian Arab; biography.
Salman Abu Sitta was just ten years old when the Nakba--the mass expulsion of Palestinians in 1948--happened, forcing him from his home near Beersheba. Like many Palestinians of his generation, this traumatic loss and his enduring desire to return would be the defining features of his life from that moment on. Abu Sitta vividly evokes the vanished world of his family and home on the eve of the Nakba, giving a personal and very human face to the dramatic events of 1930s and 1940s Palestine as Zionist ambitions and militarization expanded under the British mandate. He chronicles his life in exile, from his family's flight to Gaza, his teenage years as a student in Nasser's Egypt, his formative years in 1960s London, his life as a family man and academic in Canada, to several sojourns in Kuwait. Abu Sitta's long and winding journey has taken him through many of the seismic events of the era, from the 1956 Suez War to the 1991 Gulf War. This rich and moving memoir is imbued throughout with a burning sense of justice and a determination to recover and document what rightfully belongs to his people, given expression in his groundbreaking mapping work on his homeland. Abu Sitta, with warmth and wit, tells his story and that of Palestine. -- Back cover.
Includes bibliographical references.
Keywords: 1948-1949; Beersheba( Palestine ) -- History; Refugees, Arab; Palestinian Arabs; Jewish-Arab relations; Israel-Arab War, 1948-1949 -- Personal narratives, Palestinian Arab; Jewish-Arab relations; Palestinian Arabs; Refugees, Arab; Refugees, Palestinian Arab; Biographies; Personal narratives -- Palestinian Arab